Wide range calibration method for direct interface circuits and application to resistive force sensors - Hidalgo-López, José Antonio; Oballe-Peinado, Óscar; Castellanos-Ramos, Julián; Tejero-Calado, Juan Carlos; Vidal-Verdú, Fernando (Institute of Electrical and Electronics Engineers, 2021)
A novel approach to interface resistive sensors directly to a Field Programmable Gate Array (FPGA) is presented in this paper. The circuit is based on Direct Interface Circuits (DICs), which make the sensor reading through a magnitude-to-time-to-digital conversion using just a few passive elements and a programmable digital device. Specifically, the system uses two calibration resistors of known value, two capacitors, and a new equation to estimate the sensor resistance in order to obtain an improved estimation in both the high and low parts of the resistance range. Furthermore, the new method can be used for reading resistive force sensors, with the advantage that the equations can be adapted for the output to directly provide the force exerted, thus avoiding the need for a resistance-to- force conversion. The circuit has been implemented using an FPGA as the programmable digital device to characterize the system, which allows both the reading of discrete resistors and those of a commercial force sensor. When discrete resistors are measured, estimation error in the low part of the range (a few hundred ohms) is reduced between twofold and fivefold compared to the results provided by other DICs. Moreover, the most significant errors produced by the new method when reading a force sensor come in the high part of the range (several tens of Newtons), standing at just 0.88%, compared to errors between 1.94% and 5.23% of other methods proposed in the literature.
Keywords: Detectores; Direct Interface Circuits; Interface Sensor; Resistive Sensor; Time-Based Measurement